Strategic Directions for Regenerative Urban Tourism in North Jakarta: An SLR-FGD and TOWS-Based Assessment - Dewi Gita Kartika; Ismayanti Ismayanti; Emilia Agustina; Fernando Adiputra Kadajaya Bos (Centre of Excellence in Tourism Udayana University, 2026)
Urban coastal destinations face mounting pressures from environmental degradation, infrastructure limitations, and fragmented governance, while the application of regenerative tourism in dense metropolitan contexts remains limited. This study examines how regenerative urban tourism can be strategically developed in North Jakarta. The study applies a stepwise approach: a systematic literature review (SLR) to identify key concepts, followed by focus group discussions (FGDs) with stakeholders, such as government, tourism managers, community representatives, and MSMEs, to capture local conditions, the results are then evaluated using IFE–EFE matrices and synthesized through a TOWS analysis to formulate strategies. The findings indicate that North Jakarta has relatively strong internal capacity (IFE = 3.04) and a favorable external environment (EFE = 3.16), placing it in a “grow and build” position. Strategic priorities include developing eco-tourism and urban farming based on community greening initiatives, strengthening interactive cultural and heritage-based tourism, enhancing MSME digital capacity, and addressing environmental and infrastructure constraints such as waste management, flooding, and accessibility. This study contributes by demonstrating how regenerative tourism principles can be operationalized in an urban–coastal setting, offering a structured basis for strategy formulation in similar metropolitan destinations. Overall, the research emphasizes the need for integrative, community-driven, and climate-adaptive approaches that align ecological restoration with cultural continuity and inclusive economic growth.